(untitled) (Revista de Estudos da Linguagem, 2024)
This paper presents a proposal for pedagogical use of MT in English for Specific Purpose (ESP) courses, aiming at investigating the efficiency of this technology as a support for reading scientific texts in English as a FL. The theoretical approach is on ESP, reading and comprehension and a proposal to use MT in ESP courses, aiming to understand the processing of MT and how this knowledge can raise benefits on reading comprehension for academic purposes. In addition, we discussed corpus linguistics and its relation to language teaching as well as its role in MT. The analysis shows that, due to the hybrid system that utilizes the rule-based system and the corpus-based system, Google Translate produces relatively understandable and readable texts. Despite its evident limitations, the tool can provide linguistic awareness when pedagogically explored by ESP teachers in academic context.